IMPROVEMENT OF HYDROCHLORIC ACID TREATMENT TECHNOLOGY FOR GAS WELLS WITH ULTRA-LOW RESERVOIR PRESSURE (Innovative technologies, 2026)
This article examines the issues of improving the efficiency of chemical treatment of productive formations in oil and gas wells. Due to the shortage of hydrochloric acid and the increase in its cost, the possibility of using phosphoric acid for treating productive formations was investigated. Laboratory experiments were carried out on carbonate rock samples taken from the Sho‘rtan field, and the dissolving properties of phosphoric acid at various concentrations were studied. According to the research results, 20–25% phosphoric acid was found to have an effective impact on carbonate rocks and to produce results close to those of hydrochloric acid. In addition, when AF 9-12 and other surfactants were used, deeper penetration of the acid mixture into the formation and a reduction in metal corrosion were observed. Based on the obtained results, the feasibility of using phosphoric acid in the chemical treatment of productive formations in the near-wellbore zone of oil and gas wells was substantiated.
Keywords: oil and gas wells; productive formation; phosphoric acid; hydrochloric acid; chemical treatment; surfactants; AF 9-12; carbonate rocks; permeability; corrosion; near-wellbore zone; stimulation of oil and gas flow